Psychosocial Experiences and Support Resources of People With Albinism: A Thematic Synthesis - Taher Alizadeh; Bahman Bahmani; Mohammadsaeed khanjani; Manouchehr Azkhosh; Shima Shakiba; Mohsen Vahedi (University of Social Welfare and Rehabilitation Sciences, 2024)
Objective Albinism is a genetic disease that causes vision limitations and skin and hair problems as a result of a disorder in melanin conversion. This disease can have wide psychosocial consequences among the sufferers. This study reviews and investigates the psychosocial experiences of people with albinism. Materials & Methods This study is a review type and a thematic synthesis. This review examined the qualitative articles published until February 2023 in Persian and English in the field of psychosocial experiences of people with albinism. Articles related to extensive search were selected in PubMed, Scopus, Web of Science, SID, and Magiran databases, as well as the Google Scholar search engine. Results In the first stage of the search, 868 articles were obtained, after removing duplicate and unrelated items and checking the titles and abstracts of the articles, 365 articles were omitted and 102 articles remained. By combining the codes of qualitative articles related to the psychosocial experiences of albinism, two main themes were obtained with the titles of psychosocial challenges of people with albinism (PWA) and support resources and coping strategies in people with albinism. Conclusion PWA experience many challenges in life and they are equipped with some support resources and coping strategies to deal with these challenges, which reduces the difficulty of the mentioned challenges. Knowing these psychosocial challenges and support resources can help professionals and individuals who deal with PWA to make policies and plan and develop treatment and rehabilitation programs to create favorable and effective conditions.